Community Structure of Phytoplankton in The Bongkok River of Kubu Raya Regency, West Kalimantan - Armawati Armawati; Entin Daningsih; Wolly Candramila (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Located around the Mangrove Production and Protection Forest in Tanjung Harapan Village, Kubu Raya Regency, the Bongkok River quality needs to be studied to determine the quality of the river. This study aims to determine the physicochemical quality of water and the community structure of phytoplankton in the Bongkok River during the dry and rainy seasons. The survey method was used at three stations and 9 observation points in both seasons. Phytoplankton types are identified up to the species level. The physicochemical factors observed included temperature, transparency, water flow, pH, salinity, dissolved oxygen, dissolved carbon dioxide, and levels of nitrate and phosphate. The community structure is seen from the abundance, diversity, uniformity, and dominance index values. From a physicochemical perspective, the Bongkok River is a brackish water type with relatively low levels of phosphate and nitrate nutrients and high dissolved CO2, but dissolved oxygen is still good enough to support aquatic life. There are 41 phytoplankton species from 6 classes, including Bacillariophyceae, Chlorophyceae, Cyanophyceae, Dinophyceae, Euglenaphyceae, and Xanthophyceae. The phytoplankton abundance in the dry season is higher than in the rainy season but is still at a low to moderate level. The phytoplankton diversity in the Bongkok River is in the medium category (2.46 – 2.67) but has a high evenness (0.72-0.89) and low dominance (0.11-0.18). Overall, the water conditions in the Bongkok River are sufficient to support the life of aquatic biota. However, the abundance of phytoplankton is still at a low to moderate level, especially during the rainy season.